Pengendalian Jamur Ganoderma dengan Metode Perbanyakan Jamur Trichoderma pada Pembibitan Kelapa Sawit di PT PP London Sumatra Bah Lias Research Station - Utami, Mutiara Alya; Nasution, Rizki Amelia; Mawaddah, Fitri Asyiatun; Aulia, Rahma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Ganoderma sp. generally attacks the roots or base of the tree, whether it's alive or dead. There are also other species of Ganoderma whose caps attach directly to the tree. If Ganoderma grows on wood or a tree, then it falls into the category of